Managing against the Development of Herbicide-Resistant Weeds: Sugarcane - Dennis C. Odero; Brent A. Sellers; Jason A. Ferrell; Gregory E. MacDonald (EDIS)
Profitable sugarcane production in Florida requires effective weed management. Herbicides provide an efficient and cost-effective means of weed control, but excessive use of a single herbicide or group of herbicides with the same mechanism of action has resulted in the development of herbicide-resistant weeds. In crops such as sugarcane where a limited number of herbicides are registered, the loss of a single effective herbicide can be very costly. Thus, it is critical to manage herbicides in order to prevent or delay the development of herbicide-resistant weed populations. This revised 4-page fact sheet lists herbicides by group number, mechanism of action, chemical family, common name, and trade name. Written by D.C. Odero, B.A. Sellers, J.A. Ferrell, and G.E. MacDonald, and published by the UF Department of Agronomy, October 2014.